O dwu odmianach metody Pohlhausena i ich zastosowaniu do przepływu w sąsiedztwie punktu spiętrzenia - Prosnak, W.J.; Klonowska, M.E. (Engineering Transactions, 1968)
This paper contains a description of two variants of the Pohlhausen’s method and their application to the stagnation flow point at a moving wall. The two variants differ by the «compatibility» condition which is a conclusion from the boundary layer equations and concerns the derivative of the flow velocity at the wall. It is shown that those of the polynomials representing in an approximate manner the velocity distribution in the layer that satisfy the compatibility condition describe the boundary layer, in the case considered, in a worse manner than those that do not satisfy the compatibility condition. This result contradicts the conclusion of Hugelman’s paper, [1], and is independent of the degree N of the approximation polynomial. In any case it is valid for N = 4; 6; 8.